EVALUASI SISTEM PENGENDALIAN INTERNAL BERDASARKAN COSO INTERNAL CONTROL FRAMEWORK (Studi Kasus Pada Rumah Sakit Umum Daerah Panembahan Senopati Bantul) - , NANO ADHI WICAKSONO, Prof. Dr. Slamet Sugiri, M.B.A., C.M.A., Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The bigger a company will increase the risk of failure. The need for internal control to prevent the risk is becomes higher. Lately, the health institutions under the spotlight due to some cases. One is a case of alleged malpractice in Manado. This case shows that people have started to critical and demand hospital always give maximum services. In Bantul, Panembahan Senopati Hospital is the largest hospital with an average increase of 30 % of patients per year. This study aims to assess the operational risks of Panembahan Senopati Hospital and assess management compliance against the COSO Internal Control Framework with the assumption that Sistem Pengendalian Internal Pemerintah is adopted from COSO Internal Control Framework. The study was conducted with a qualitative approach. The method of data collection was done by the study of literature through theoretical analysis of various sources and secondary data analysis, and field studies with observation and interviews in a hospital environment. Interviews were conducted by a sampling of the some relevant management to this study. The interview is limited to issues of operational risk assessment and management compliance with COSO Internal Control Framework. The results showed that in risk assessment, Finance Division, Installation of PSRS, and Installation of Medical Record and SIM RS occupy the top three highrisk division. Management could response to the risks by sharing and reduce risk. The main risk which is faced by hospitals is the effectiveness and efficiency of operations due to cash flow problem in the hospital. Then, in general, management compliance with COSO Internal Control Framework has been good enough, but require further improvement. The most important issue is hospitalâs Satuan Pengawas Intern (SPI) did not operate. Researchers advised to cooperate with the public accounting firm to create the form of Internal Audit Charter as a basis, and run the SPI based on it.